José Pascual Buxó, Sor Juana Inés de la Cruz. Lectura barroca de la poesía. Editorial Renacimiento, Madrid, 2006; 401 pp. - Bravo Arriaga, María Dolores (El Colegio de México, 2008)
Se reseñó el libro: Sor Juana Inés de la Cruz. Lectura barroca de la poesía.